2001
DOI: 10.1177/088626001016004001
|View full text |Cite
|
Sign up to set email alerts
|

Date Rape Prevalence Among Female High School Students in a Rural Midwestern State During 1993, 1995, and 1997

Abstract: The purpose of this study was to estimate the prevalence of date rape among a statewide, random sample of female high school students. A date rape item was included on the Youth Risk Behavior Survey questionnaire administered to random samples of South Dakota high school students during 1993, 1995, and 1997. The prevalence of date rape among female high school students in the three statewide samples ranged from 11.8% to 14.9%. Due to measurement limitations, these results are likely to underestimate the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…Prevalence rates for adolescent dating violence vary from 9%-77% for girls and 6%-67% for boys (Ackard and Neumark-Sztainer, 2002;Bergman, 1992;Schubot, 2001;Vicary et al, 1995); the wide range of estimates is likely the result of variation in the definition of violence, with some studies measuring personal insults (e.g., "put down my looks"), and others measuring only the most serious forms of violence, such as physical or forced sex. It is important to note that adolescent girls engage in aggressive behaviors toward dating partners at rates that are comparable to, or exceed, those for boys when considering verbal, emotional, physical, and sexual aggression in conjunction (Chase et al, 2002).…”
Section: Romantic Relationships and Acquaintance Assault Among Adolesmentioning
confidence: 99%
“…Prevalence rates for adolescent dating violence vary from 9%-77% for girls and 6%-67% for boys (Ackard and Neumark-Sztainer, 2002;Bergman, 1992;Schubot, 2001;Vicary et al, 1995); the wide range of estimates is likely the result of variation in the definition of violence, with some studies measuring personal insults (e.g., "put down my looks"), and others measuring only the most serious forms of violence, such as physical or forced sex. It is important to note that adolescent girls engage in aggressive behaviors toward dating partners at rates that are comparable to, or exceed, those for boys when considering verbal, emotional, physical, and sexual aggression in conjunction (Chase et al, 2002).…”
Section: Romantic Relationships and Acquaintance Assault Among Adolesmentioning
confidence: 99%
“…In her nationally representative sample of college students, Koss (1988) found that about 27% of women have experienced rape or attempted rape since the age of 14 and 57% of these sexual assaults occurred during a date. Schubot's (2001) study using a random sample of South Dakota high school students in 1997 reported that almost 12% of female respondents had been forced to have sexual intercourse on a date. Of the few resources available, statistics show that date rape is a problem in South Korea as well.…”
Section: Introductionmentioning
confidence: 98%
“…These factors come to bear on young men and women as they begin to mature, increasing the likelihood of both the use of force and victimization by force among children learning to manage emerging sexuality. It is thus not surprising that in his measure of self-reported rape from high school students in South Dakota for three years (1993, 1995, and 1997), Schubot (2001) found rates ranging from 11.8 percent to 14.9 percent. In the area of sexual assault, Acierno et al (2001) found that younger women report higher levels of assault than older women.…”
Section: Intimate Violence In High Schoolsmentioning
confidence: 90%